Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ferroptosis modulation by Toxoplasma gondii suppresses sodium iodate–driven age-related macular degeneration - Xin-Cheng Wang; Guan-Hao Hong; Yu-Sun Yun; In-Wook Choi; Jaemin Yuk; Guang-Ho Cha (Genes & Genomics, 2026)

A Dual-Modality nanozyme Exploiting ROS-Responsive oxygen Catalysis for Precision NF-κB pathway Suppression in gouty arthritis - Sathiyamoorthy Padmanaban; Sree Samanvitha Kuppa; Omkar Sangabathula; Amal Babu; Adityanarayan Mohapatra; Sung Sun Kim; Hong Yeol Yang; Aravindkumar Sundaram; Hyung Keun Kim; Jong Keun Seon; In-Kyu Park (Chemical Engineering Journal, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Enhancing the performance of Litopenaeus vannamei nursery and grow-out by modifying Mg/Ca ratios in biofloc systems using low-salinity groundwater of Kuwait Desert - Sherain N. Al-Subiai; In Kwon Jang; Sun-Hye Bae; Hong-seok Yoon; Sumaiah Hussain; Sabeekah AlNuaimi; Muhammad Al-Foudari; Enas Al-Hasan (Aquaculture, 2025)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Correction to: Microbacterium aquilitoris sp. nov. and Microbacterium gawkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yan; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

Mechanochemical activation of silicon photothermal material for efficient interfacial solar desalination and wastewater purification - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Jong Ho Lee; Seo Yeong Hong; Yoo Jae Jeong; Seong Sik Shin; In Sun Cho (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Microbacterium aquilitoris sp. nov. and Microbacterium gwkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yang; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Defect-enriched red phosphorus nanosheets as efficient and stable photothermal absorber material for interfacial solar desalination - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Runfa Tan; Seo Yeong Hong; Dong Hoe Kim; In Sun Cho (Desalination, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

First report of powdery mildew caused by Podosphaera xanthii on Matricaria chamomilla in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

First report of powdery mildew caused by Erysiphe polygoni on Rumex japonicus in Korea - In-Young Choi; Hyun-Myung Oh; Sun-Hee Hong; Young-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

Assessment of the abuse potential of methamnetamine in rodents: a behavioral pharmacology study - Dong-Hyun Youn; Jin Mook Kim; Young-ki Hong; Seo-In Park; Jin-Moo Lee; Young-Hoon Kim; Chang Won Park; Mi Sun Kang (Psychopharmacology, 2021)

Pollen-mediated flow of bar gene in transgenic herbicide-resistant turf grass Zoysia japonica - Hong-Gyu Kang; Ok-Chul Chung; Tae-Woong Bae; Hyeon-Jin Sun; In-Ja Song; Kee Woong Park; Pyung-Ok Lim; Jaechun Lee; Yong-Eok Lee; Pill-Soon Song; Hyo-Yeon Lee (Plant Biotechnology Reports, 2021)

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

First report of powdery mildew caused by Podosphaera erigerontis-canadensis on Conyza sumatrensis in Korea - In-Young Choi; Sun-Hee Hong; Yong-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

Comparison of the clinical characteristics and outcomes of bloodstream infections caused by Raoultella species and Klebsiella pneumoniae - Kyung-Wook Hong; Yun-Hong Cheon; Kyunglan Moon; Sun In Hong; Byung-Han Ryu; Oh-Hyun Cho; In-Gyu Bae (Infectious Diseases, 2020)

Vildagliptin, an Anti-diabetic Drug of the DPP-4 Inhibitor, Induces Vasodilation via Kv Channel and SERCA Pump Activation in Aortic Smooth Muscle - Mi Seon Seo; Hongliang Li; Jin Ryeol An; In Duk Jung; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

Functional roles of the pepper leucine-rich repeat protein and its interactions with pathogenesis-related and hypersensitive-induced proteins in plant cell death and immunity - Jeum Kyu Hong; In Sun Hwang; Byung Kook Hwang (Planta, 2017)

Investigation into effects of transgenic glufosinate-resistant Zoysia grasses with herbicide application on bacterial communities under field conditions - Yong-Eok Lee; Sun Hwa Lee; Gil-Do Ryu; Hong-Gyu Kang; Yong-Ik Kwon; Hyeon-Jin Sun; Kee Woong Park; Bumkyu Lee; In-Ja Song; Pyung-Ok Lim; Hyo-Yeon Lee (Journal of Plant Biology, 2015)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

Overexpression of a Brassica rapa MADS-box gene, BrAGL20, induces early flowering time phenotypes in Brassica napus - Joon Ki Hong; Soo-Yun Kim; Kwang-Soo Kim; Soo-Jin Kwon; Jung Sun Kim; Jin A. Kim; Soo In Lee; Yeon-Hee Lee (Plant Biotechnology Reports, 2013)

Overexpression of Brassica rapa SHI-RELATED SEQUENCE genes suppresses growth and development in Arabidopsis thaliana - Joon Ki Hong; Jin A. Kim; Jung Sun Kim; Soo In Lee; Bon Sung Koo; Yeon-Hee Lee (Biotechnology Letters, 2012)

Reexamination of the genus Pterocladiella (Gelidiaceae, Rhodophyta) in Korea based on morphology and rbcL sequences - Sung-Min Boo; Su-Yeon Kim; In-Sun Hong; Il-Ki Hwang (Algae, 2010)

Test of a convectively forced gravity wave drag parameterization in a general circulation model - Jong-Hun Jeon; Song-You Hong; Hye-Yeong Chun; In-Sun Song (Asia-Pacific Journal of Atmospheric Sciences, 2010)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

A novel pepper membrane-located receptor-like protein gene CaMRP1 is required for disease susceptibility, methyl jasmonate insensitivity and salt tolerance - Soo Hyun An; Hyong Woo Choi; In Sun Hwang; Jeum Kyu Hong; Byung Kook Hwang (Plant Molecular Biology, 2008)

Function of a novel GDSL-type pepper lipase gene, CaGLIP1, in disease susceptibility and abiotic stress tolerance - Jeum Kyu Hong; Hyong Woo Choi; In Sun Hwang; Dae Sung Kim; Nak Hyun Kim; Du Seok Choi; Young Jin Kim; Byung Kook Hwang (Planta, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Acute hypoxia induces vasodilation and increases coronary blood flow by activating inward rectifier K+ channels - Won Sun Park; Youn Kyoung Son; Nari Kim; Jae-Hong Ko; Sung Hyun Kang; Mohamad Warda; Yung E. Earm; In Duk Jung; Yeong-Min Park; Jin Han (Pflügers Archiv - European Journal of Physiology, 2007)

Fengshui theory in urban landscape planning - Sun-Kee Hong; In-Ju Song; Jianguo Wu (Urban Ecosystems, 2007)

Role of a novel pathogen-induced pepper C3–H–C4 type RING-finger protein gene, CaRFP1, in disease susceptibility and osmotic stress tolerance - Jeum Kyu Hong; Hyong Woo Choi; In Sun Hwang; Byung Kook Hwang (Plant Molecular Biology, 2007)

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling - Min-Ju Chae; Jung-Sook Lee; Myung-Hee Nam; Kun Cho; Ji-Yeon Hong; Sang-A Yi; Seok-Cheol Suh; In-Sun Yoon (Plant Molecular Biology, 2006)

Characterization of copper, zinc superoxide dismutase from a cartilaginous shark species, Scyliorhinus torazame (Carcharhiniformes) - Yoon Kwon Nam; Young Sun Cho; Keun-Yong Kim; In Chul Bang; Ki Hong Kim; Sung Koo Kim; Dong Soo Kim (Fish Physiology and Biochemistry, 2006)

Applications of biotope mapping for spatial environmental planning and policy: case studies in urban ecosystems in Korea - Sun-Kee Hong; In-Ju Song; Byungseol Byun; Sanglim Yoo; Nobukazu Nakagoshi (Landscape and Ecological Engineering, 2005)

p53 and cell-cycle-regulated protein expression in small intestinal cells after fast-neutron irradiation in mice - Young-Heun Jee; Won-Il Jeong; Tae-Hwan Kim; In-Sun Hwang; Mee-Jung Ahn; Hong-Gu Joo; Su-Hyung Hong; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2005)

Intermittent maltose feeding enhances paclitaxel production in suspension culture of Taxus chinensis cells - Hyung-Kyoon Choi; Sang-Ic Kim; Joo-Sun Son; Seung-Suh Hong; Hyun-Soo Lee; In-Sik Chung; Hyong-Joo Lee (Biotechnology Letters, 2000)

Karyotypes of three somaclonal variants and wild plants ofAllium tuberosum by bicolor FISH - Geum-Sook Do; Bong-Bo Seo; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Journal of Plant Biology, 2000)

Ultrastructure of leaves in C4 Cyperus iria and C3 Carex siderosticta - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Ultrastructural aspects of leaves inFestuca ovina andPoa sphondylodes (C-3 Poaceae) - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1998)